2013
DOI: 10.1097/ftd.0b013e318290eacc
|View full text |Cite
|
Sign up to set email alerts
|

Lacosamide Therapeutic Monitoring in Patients With Epilepsy

Abstract: Our findings confirm, in a real-patient clinical setting, preliminary evidence from randomized, clinical trials showing that carbamazepine, phenobarbital, or phenytoin significantly reduces the overall systemic exposure to LCM. From a practical point of view, patients on concomitant AED strong inducers may require a 30% higher dose of LCM compared with patients not receiving strongly inducing AED cotherapy, to achieve the same plasma drug concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“… 30 , 31 A Norwegian study with 344 patients and an Italian study with 75 patients found that nearly all patients with good therapeutic effect had drug-fasting serum concentrations within a range of 10–40 μmol/L (3–10 mg/L). 32 , 33 We, therefore, recommend that the current reference range remains unchanged.…”
Section: Resultsmentioning
confidence: 99%
“… 30 , 31 A Norwegian study with 344 patients and an Italian study with 75 patients found that nearly all patients with good therapeutic effect had drug-fasting serum concentrations within a range of 10–40 μmol/L (3–10 mg/L). 32 , 33 We, therefore, recommend that the current reference range remains unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…The use of perchloric acid to deproteinize [14] was also avoided. The deproteinization with methanol described by Contin M, et al [10] was performed, but a pressure increase was observed in the chromatographic system after a small number of samples were injected. Thus, pretreatment with methanol was abandoned.…”
Section: Discussionmentioning
confidence: 99%
“…Good chromatographic separation was achieved when preparing the potassium dihydrogen phosphate buffer at a concentration of 10 mM instead of 50 mM [10], contributing to the use of less reagents. The flow rate of the mobile phase in the present method was lower than in other methods of 0.8 mL/min [9], 1 mL/min [7,12,19], 1.2 mL/min [13,14], and 1.5 mL/min [10]. Besides, other methods have longer runtimes of 10 [9], 14 [10], 17 [12] and 18 minutes [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population pharmacokinetic data from phase II clinical studies of lacosamide have shown that lamotrigine, levetiracetam, topiramate, oxcarbazepine, and VPA have no significant effects on the pharmacokinetics of lacosamide [65]. Enzyme inducers such as carbamazepine and phenytoin can significantly reduce plasma lacosamide concentrations and thereby enhance clearance [66, 67]. Although data are limited, overall, lacosamide does not affect the pharmacokinetics of many AEDs [60].…”
Section: Newest Antiepileptic Drugsmentioning
confidence: 99%